2016
DOI: 10.3311/ppme.8734
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of an FG Plate Behavior Impacted at Low Velocity in a Temperature Field

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Their study indicated that the elastoplastic behavior of the functionally graded plate is mainly affected by the impactor velocity, plate radius, and compositional gradient exponent. In addition, Khalili et al, 23 Kiani et al, 25 Smahat and Megueni 26 discussed the effect of temperature, compositional gradient exponent, and impactor velocity on the performance of ballistic protections composed of functionally graded plates under low-velocity impacts. It has been found that each of these parameters has significant effect on the impact characteristics which should be considered during the design process and further in the performance evaluation of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Their study indicated that the elastoplastic behavior of the functionally graded plate is mainly affected by the impactor velocity, plate radius, and compositional gradient exponent. In addition, Khalili et al, 23 Kiani et al, 25 Smahat and Megueni 26 discussed the effect of temperature, compositional gradient exponent, and impactor velocity on the performance of ballistic protections composed of functionally graded plates under low-velocity impacts. It has been found that each of these parameters has significant effect on the impact characteristics which should be considered during the design process and further in the performance evaluation of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The nonhomogeneous material described above is closest to the Functionally Graded Materials (FGMs) now is popular in academic circles. As a rule, the properties of such materials are set as a continuous function from one phase to another, implying that the sizes of the zones are comparable [7][8][9]. Many studies have been carried out within the framework proposed by Biot [10], the classical conventional coupled theory of thermal elasticity.…”
Section: Introductionmentioning
confidence: 99%